Strategi Guru Christian Education dalam Membentuk Karakter Siswa melalui Character Education: Penelitian - Faldin Adrianus Bunga; Annesya Sibagariang; Nehemia Februari Purba; Maestro Pedro Viandito; Naomi Yolanti Octavia Ritonga; Selvinus Yohame (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to explore the strategies of Christian Education teachers in shaping students' characters through character education. The method used is qualitative descriptive which can lead to character and spiritual education with a library approach by collecting theories and information from various sources such as journals, online media websites and other sources. The results of the study indicate that the formation of student character can be strengthened through approaches such as teacher role models, integration of Christian values ​​in the curriculum, giving awards for positive behavior, and spiritual guidance. These strategies not only improve the quality of learning, but also support the development of student character in accordance with Christian teachings. This study emphasizes the importance of the role of teachers as moral and spiritual role models, while providing recommendations for the implementation of more effective character education strategies in religious schools.